A companion to Boniface - Aaij, Michel; Godlove, Shannon (Brill's companions to the Christian tradition, 2020)
"The eighth-century English missionary and church reformer Boniface was a highly influential figure in early medieval Europe. His career in what is now Germany, France, and the Netherlands is attested in an exceptional number of textual sources: a correspondence of 150 letters, Latin poetry church council records, and other documents. Numerous saints' live and modern devotional materials further reveal how he was and is remembered by the religious communities that claim him as a foundational figure. This volume comprises the latest scholarshiop on Boniface and his fellow missionaries, examining the written materials associated with Boniface, his impacts on the regions of Europe where he worked (Hessia, Thuringia, Bavaria, Frisia, and Francia), and the development of his cult in the MIddle Ages and today."--Back cover